Personality Profile - Lohani, Bindu N. (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
With an objective to highlight the prominent Nepali personalities who have played important roles in major donor agency, Asian Development Bank (ADB), HYDRO Nepal Journal considers it appropriate to underline the profile of Dr. Bindu N. Lohani to its readers. HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue No: 22Page: 53-53Uploaded date: January 14, 2018